Warehouse operations: storage and delivery process at Total Logistic Services (M) Sdn. Bhd / Faiqah Mawardi, Hawa Husna Ab Ghani and Nur Izatul Irani Selim - Mawardi, Faiqah; Ab Ghani, Hawa Husna; Selim, Nur Izatul Irani (Faculty of Business Management, 2013)
This research examines storage and delivery process at Total Logistic Services (M) Sdn. Bhd and the scope of study is at TLS’s SA2 warehouse. The research concentrates the application process on storage and delivery process, and the problems arise during the part movement from 2010 to 2012. This research discusses some of the possible factors implemented by the company in order to identify the problems. In order to achieve the research objective, four questions were addressed. There are (i) How does the implement for storage and delivery process at the TLS’s SA2 warehouse?; (ii) What are the problems faced at SA2 warehouse?; and (iii) What are the factors that causing these problems at SA2 warehouse?; (iv) What are the recommendations suggested to the TLS’s SA2 warehouse to solve problem faced?. This research takes a qualitative approach in collecting the primary data from interviews as well as observations because this is the most appropriate way to conduct a firm level study. Secondary data such as the company’s performance reports and departments’ operational records were used for ensuring that the result of this research is valid and precise. The respondents involved in the interviews are the staff which responsible in managing the storage and delivery area. Findings on storage and delivery process, type of problems as well as the factors that cause problems are illustrated in figures and tables. Samples of documentation, procedure, process, inspection, and problem reports are attached for reference. This research concludes that part damages are common problems in handling part movement for storage (segregation, unpacking, staging); and delivery (packing, devanning, delivery) process. These are due to lack of commitment in 5’S practices and provision of training to staff. This paper ends with the possible solutions that can be executed in order to help the company to achieve the targeted operation performance.